Selection and purification of Li2CO3 precursor for bolometric double beta decay experiments - Shin, KeonAh; Byeon, Chorok; Choe, JunSeok; Gileva, Olga; Kim, Yena; Kim, Yeongduk; Lee, Eunkyung; Lee, Moo Hyun; Yeon, Hyojin (Frontiers in Physics, 2024)
This paper describes the preparation of radiopure lithium carbonate powder for the needs of lowbackground research, in particular, AMoRE-II, the second phase of a search for the neutrinoless double-beta decay (0DBD) of the 100 Mo isotope using over 100 kg of 100 Mo contained in 200 kilograms of ultra-pure Li2 100 MoO4 bolometric crystals. About 150 kg of pure Li2CO3 powder is required to synthesize the crystals. The desired radiopurity for the lithium powder is 40 K below 100 mBq/kg, and Th/U and Ra are at a few mBq/kg. Several commercially available powders were tested with ICP-MS and HPGe detectors at the Center for Underground Physics (CUP) of the Institute for Basic Science in Korea. The lowest purity of the tested products was 99.99%. The results of the powders' radioassay at CUP showed that none of the tested products were suited for the 0DBD search application. A special purification technology had to be developed to remove the original contamination of the powder with potassium (K), thorium (Th), uranium (U), and radium (Ra). Lithium carbonate crystallization via carbonization technique was inefficient in removing radiochemical impurities. Lithium formate fractional recrystallization effectively removed Ra, K, and Th, but the synthesis of the final lithium carbonate product had a low yield and required the introduction of additional chemicals. The analysis results of raw and purified powders, the decontamination efficiency, and plans are described in the article.